Design and Control of Modified Resonant Voltage Multiplier Rectifier for Photovoltaic Applications Using Electrolytic Capacitive Material - Shanmugam, Sathish Kumar; Reddy, C. Subba Rami; PRASAD, S. V. G. V. A.; Narukullapati, Bharath Kumar; Ramkumar, R.; RajaSekhar, G. G.; Subramaniam, G.; Sivachitra, M.; Anbarasu, L.; Ladu, Nyagong Santino David (Journal of nanomaterials, 2022)
In this paper, a modified resonant voltage multiplier rectifier (RVMR) has been developed to improve the voltage gain and efficiency of the proposed converter on PV interconnected renewable energy systems. To acquire the most energy from the PV source, the improved RVMR scheme uses an altered Perturb and Observe (P&O)-based MPPT approach. This paper develops a modified variable step size P&O MPPT algorithm that can increase the PV system’s dynamic and steady-state performance at the same time. The recommended variable step size technique addresses the constraints of traditional P&O MPPT. The suggested study uses the MATLAB/Simulink environment to analyze and evaluate voltage gain and efficiency.